Comparison of General Anesthesia vs Spinal Anesthesia on Post Operative Pain After Hysterectomy - A Systematic Review and Meta-analysis - Lalchanzani, Jawaharlal Akbar; Faida, Nova Auliyatul; Auzan, Asyrafly (Journal of Anaesthesia and Pain, 2026)
Background: Hysterectomy is among the most frequently performed major surgical procedures. General anesthesia (GA) remains the most commonly used technique. The choice between GA and spinal anesthesia (SA) can significantly impact patient outcomes, particularly pain control and the incidence of postoperative nausea and vomiting. This systematic review and meta-analysis aims to compare the effects of GA versus SA on duration of operation, pain intensity, postoperative analgesic consumption, and the incidence of nausea and vomiting in patients undergoing hysterectomy. Methods: This systematic review and meta-analysis assessed operative duration, pain intensity, postoperative analgesic consumption, and the incidence of nausea and vomiting in GA versus SA for hysterectomy. Data were analyzed using random‑effects models.   Result: Eight studies, including a total of 1,054 patients, were analyzed. Postoperative pain intensity was significantly higher in the GA group based on the Visual Analogue Scale (VAS) score compared to the SA group (MD, 0.84; 95% CI, [0.11, 1.56]; p = 0.02, I² = 56%). No significant differences were found for other outcomes: operative time (MD, 1.95; 95% CI, [-1.30, 5.19]; p = 0.24, I² = 10%), analgesic consumption (MD, -7.48; 95% CI, [-20.38, 5.43]; p = 0.26, I² = 96%), and nausea/vomiting events (RR, 0.71; 95% CI, [0.48, 1.05]; p = 0.09, I² = 0%). Conclusion: SA showed significant reductions in pain scores compared with GA, suggesting potential benefits for pain relief. However, the choice of anesthesia should be guided by patient-specific factors, the complexity of the surgery, and clinical preferences.